Functional, malignant intrathoracic paraganglioma. Issue 761 (March 1989) - Aggarwal, P.; Wali, J. P.; Venugopal, P.; Khosla, A.; Tickoo, S. K.
Abstract : This paper describes a case of functional, malignant branchiomeric paraganglioma, the third such to be reported. The patient presented with malignant hypertension and symptoms suggestive of excessive catecholamine secretion.